# What is the value of x in the equation 2(x - 3) + 9 = 3(x + 1) + x?

**Solution:**

Given Equation is:

2(x - 3) + 9 = 3(x + 1) + x

On simplifying the brackets, we get

2x - 6 + 9 = 3x + 3 + x

**Writing the like terms in one side and constant on other side, we get**

2x - 3x - x = 3 + 6 - 9

-2x = 0

x = 0 / -2

= 0

**Hence the required value is 0.**

## What is the value of x in the equation 2(x - 3) + 9 = 3(x + 1) + x?

**Summary:**

The value of x in the equation 2(x - 3) + 9 = 3(x + 1) + x is 0.

Verification: If x = 0 in the given equation 2(0 - 3) + 9 = 3(0 + 1) + 0 ⇒ -6 + 9 = 3

3 = 3.